Efficient and Clean Nickel Catalyzed α‐Allylation Reaction of Nitriles. Issue 5 (8th February 2021) - Mouhsine, Bouchaib; Karim, Abdallah; Dumont, Clément; Suisse, Isabelle; Sauthier, Mathieu
Abstract: A clean method has been developed for the α‐allylation of phenyl and alpha alkyl phenyl acetonitrile with allylic alcohols. The reaction is catalyzed by nickel complexes in situ generated from a combination of Ni(cod)2 and the dppf ligand and performed at 80 °C in methanol as reaction solvent. Accordingly to this simple and base‐free protocol that only yields water as a side‐product, many allylic nitriles were synthetized with good yields. Abstract :